Effect of sodium trimetaphosphate on hydroxyapatite solubility: An in vitro study - Souza, José Antonio Santos [UNESP] (2013)
This study evaluated the effect of different concentrations of sodium trimetaphosphate (TMP) with and without fluoride (F) on the concentration of calcium (Ca), phosphorus (P) and F in hydroxyapatite (HA). Synthetic HA powder (0.15 g) was suspended (n=6) in solutions (75 mL) of TMP at 0%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1.0%, 2.0%, 4.0%, 6.0%, 8.0% and 10% concentrations in the presence and absence of 100 ppm F and subjected to a pH-cycling process. The precipitates were filtrated, dried at 70° C for 24 h and ground onto a fine powder. The concentrations of F (KOH (CaF2) and HCl (FA) soluble), Ca (Arsenazo III), and P (molybdate method) in HA were determined. The Ca P, and Ca/P ratio data were subjected to Tukey's test and the F data were subjected to Student-Newman-Keuls test (p<0.05). The addition of TMP to the samples reduced F deposition to 98% (p<0.001). The groups containing 100 ppm F and 0.4% or 0.6% TMP exhibited a higher Ca concentration than the group containing only 100 ppm F (p<0.05). Furthermore, the HA treated with 0.2% and 0.4% TMP and 100 ppm F showed a higher Ca/P ratio than the other groups (p<0.001). In conclusion, TMP at 0.2%, 0.4% and 0.6% concentrations combined with F seemed to be able to precipitate HA with low solubility. However, especially at high concentrations, TMP interferes with F deposition on HA.